Setting the Stage to Address the Dual Challenge of MDGs and NCDs - Pierre-Louis, Anne Maryse; Ferl, Katharina; Wadhwani, Christina Dinh; Harnam, Neesha; Meiro-Lorenzo, Montserrat (World Bank, Washington, DC, 2015)
The purpose of this discussion paper is to assist countries in exploring synergies in service delivery and disease dynamics that can positively affect both non-communicable diseases (NCDs) and the Millennium Development Goals (MDGs). The paper examines the challenges countries face in addressing both infectious and non-communicable diseases, and highlights examples of integrated interventions in addressing this double burden of disease. Many low- and middle-income countries are faced with a rising burden of NCDs while working to improve health outcomes to meet health-related MDGs. This dual challenge takes place in an environment of increasingly limited resources, which is why the efficient integration of prevention, diagnosis and treatment of NCDs with MDG-related activities will be, in many instances, the best option these countries will have to address such challenges. Brazil’s Family Health Program and Turkey’s Health Transformation Program provide useful examples to draw on, and have been highlighted in this paper. Both programs have demonstrated impressive results, which can serve as an impetus for countries to take action.